Postsynaptic neuronal activity promotes regeneration of retinal axons - Supraja G. Varadarajan; Fei Wang; Onkar S. Dhande; Phung Le; Xin Duan; Andrew D. Huberman (Cell Reports, 2023)
Summary: The wiring of visual circuits requires that retinal neurons functionally connect to specific brain targets, a process that involves activity-dependent signaling between retinal axons and their postsynaptic targets. Vision loss in various ophthalmological and neurological diseases is caused by damage to the connections from the eye to the brain. How postsynaptic brain targets influence retinal ganglion cell (RGC) axon regeneration and functional reconnection with the brain targets remains poorly understood. Here, we established a paradigm in which the enhancement of neural activity in the distal optic pathway, where the postsynaptic visual target neurons reside, promotes RGC axon regeneration and target reinnervation and leads to the rescue of optomotor function. Furthermore, selective activation of retinorecipient neuron subsets is sufficient to promote RGC axon regeneration. Our findings reveal a key role for postsynaptic neuronal activity in the repair of neural circuits and highlight the potential to restore damaged sensory inputs via proper brain stimulation.